The Miracle on the Han River – Can We Still Learn from the Korean Experience? A Sustainable Development Perspective - Szymczak, Magdalena (Cud nad rzeką Han – czy nadal możemy uczyć się z koreańskich doświadczeń? Perspektywa zrównoważonego rozwoju, 2024)
Aim: The article aimed at assessing Korean economic growth in line with the three pillars of sustainable development. Methodology: The authors employed basic statistical methods, literature analysis, and an examination of national and international reports and analyses. Results: Korean economic growth may be considered sustainable. However, significant problems in the social pillar should be highlighted. Implications and recommendations: The proposed original selection of indicators can be used to assess the economies of other countries. Given limited access to data, the study can be repeated based on data available only in the Korean language in the future. Originality/value: The literature often examines individual policies that impacted on Korea’s economic development and, on this basis, proposes solutions for developing countries. However, the broader discourse lacks an assessment of sustainable development beyond the economic aspect, as presented in this article.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2024; vol. 68, nr 2, s. 134-147
Keywords: sustainable development; miracle on the Han River; Korean economy; zrównoważony rozwój; cud nad rzeką Han; koreańska gospodarka